2018
DOI: 10.21608/jfds.2018.77757
|View full text |Cite
|
Sign up to set email alerts
|

Different Moisture Contents of Tempered Hull Barley and Hull-Less Barley Grains Prior to Milling 2. Effect on Physical and Sensory Properties of Bread Baked from these Barley Flours.

Abstract: The purpose of this work was to study the effect of different moisture contents (12, 14, 16 and 18%) of conditioned hull barley and hull-less barley grains prior to milling on physical and sensory properties of bread baked from these barley flours. The results indicated that the specific volume of breads baked from barley flours and wheat-barley composite flours were enhanced with increasing conditioning moisture of barley grains prior to milling; therefore baking loss values decrease. On the other hand, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
3
1
0
Order By: Relevance
“…It can be observed that, hull-less barley (Giza 130) grains was significantly higher level of starch compared with the other hulled varieties. Similar finding was reported by Abdel-Gawad et al (2016).…”
Section: Starch Contents In Barley Grainssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be observed that, hull-less barley (Giza 130) grains was significantly higher level of starch compared with the other hulled varieties. Similar finding was reported by Abdel-Gawad et al (2016).…”
Section: Starch Contents In Barley Grainssupporting
confidence: 92%
“…Results indicated that, hull-less barley (Giza 130) grains was significantly lower level of pentosan compared with the other hulled varieties. Similar finding was reported by Abdel-Gawad et al (2016). Soaking process (12h) caused a slight decrease in the pentosan content of barley samples compared with control.…”
Section: Pentosans Contentsupporting
confidence: 89%
“…Adhesivity of bread samples increases with higher β-GRF supplementation, in line with other works showing that bread containing β-glucans exhibits lower moisture loss during storage [11]. Abdel-Gawad [30] reported that β-glucan enrichment could prolong bread shelf life, and the reduction in moisture loss is evident with an increasing concentration of β-glucans. The results confirm that β-glucan can impact bread quality parameters, potentially causing some damage, as observed by other authors [31].…”
Section: Crust and Crumb Attributes And Texture Profile Of The Breadsupporting
confidence: 87%
“…The concentration of any gum and water amount were variable as shown in Table 1 and 2. Gluten-free pan bread were prepared using a straight-dough method according to Abdel-Gawad et. al., (2018).…”
Section: Preparation Of Gfpbmentioning
confidence: 99%